Efektivitas Kompres Hangat terhadap Intensitas Nyeri Punggung pada Ibu Hamil Trimester III - Ayu Restu Amalia; Erika Erika; Ari Pristiana Dewi (Holistic Nursing and Health Science, 2020)
Introduction: Providing a warm feeling to a particular area of one of the lower backs using warm water and a jar generates warmth on parts of the body to reduce pain. This study aimed to determine the effectiveness of warm compresses against back pain in third trimester pregnant women in a Public Health Center in Pekanbaru. Methods: The study used a quasi-experiment design with a non-equivalent control group research design employing a purposive sampling technique with a total sample of 30 respondents. The measuring instrument used is the Numeric Rating Scale (NRS). Statistical analysis used the dependent t-test and independent t-test. Results: Univariate analysis results showed that 90.0% of respondents were 20-35 years old, while the distribution of high school education level was 36.7%. The highest distribution of work as housewives was 43.3%, with the highest gravida status being multiparous was 50.0%. The majority of the Minang respondents were 40.0%. The highest gestational age was 30 weeks experienced by 23.3% respondents. The average pain intensity of the pretest experimental group was 4.53 and the posttest value was 3.07, with a difference of 146, while the control group pretest control group was 4.40 and posttest which was 4.07, there was no significant difference between the pre-test and post-test in the control group. The results of statistical analysis showed that p value = 0.001 <α (0.05), so it was found that the warm compress effectively reduces the intensity of back pain in third trimester pregnant women. The warm compress can be recommended as a complementary therapy for back pain.